Thriving, catching up or falling behind: Immigrant and refugee children’s kindergarten competencies and later academic achievement - Gagné, Monique; Guhn, Martin; Emerson, Scott; Magee, Carly; Milbrath, Constance; Gadermann, Anne (International Journal of Population Data Science, 2019)
Background with rationale Immigrant and refugee children and adolescents form a growing socially, culturally, and economically diverse group with varying adaptation outcomes. Main Aim In this Canadian, population-based study, we wanted to identify the varying academic achievement trajectories that immigrant and refugee children followed from childhood to adolescence (e.g., thriving, catching up, or falling behind) and whether these differences could be predicted at school entry, based upon select social/migration factors and teacher-assessed literacy, numeracy, and social-emotional competencies in kindergarten. Methods The study used a retrospective, longitudinal, population-based design and leveraged linked, individual-level administrative data from four sources (Immigration, Refugees, and Citizenship Canada, Ministry of Education, Ministry of Health, Human Early Learning Partnership) to identify a cohort of immigrant and refugee children in British Columbia, Canada (N = 9,216). We utilized a novel analytical approach (Group-based Trajectory Modeling) that allowed us to capture heterogeneity in the Grade 4 to Grade 10 academic (literacy and numeracy) trajectories. Results We found that immigrant and refugee children followed a range of academic achievement trajectories from Grade 4 to Grade 10 – some children thriving, some catching up, and others falling behind over time. A number of social/migration factors (e.g., sex and refugee status) as well as literacy, numeracy, and social-emotional competencies in kindergarten predicted these later academic trajectories in unique and sometimes powerful ways. Conclusion In all, we found that not all immigrant and refugee children start school on equal footing and this was associated with long-term outcomes. The implications for the importance of early, tailored interventions to set immigrant and refugee children onto paths of positive adaptation will be discussed.